Training on Diversifying Processed Fish Products into Meatballs and Satay for Fishermen’s Wives in Nangadhero Village, Nagekeo Regency - Yohanes Freadyanus Kasi; Maria Elisabet Ga’a; Delviana Vivi Bai; Maria Yosefina Dadi; Wilhelmina Safrin Azi; Hendrikus D. Kartiko Waja; Mohamad Zulkifli; Yuventa Hendrika Ani; Anastasia Sode; Alexandro Dando Busa (Samakta: Jurnal Pengabdian Kepada Masyarakat, 2026)
This community service activity aimed to improve the knowledge and skills of fishermen’s wives in Nangadhero Village in diversifying processed fish products into fish meatballs and fish satay as value-added products. The program was conducted using the Participatory Action Research (PAR) approach through the stages of problem identification, socialization, training, hands-on practice, and evaluation. A total of eight fishermen’s wives participated in the training. Program evaluation was carried out through direct observation of participants’ practical skills in each stage of fish processing, complemented by discussions and feedback sessions. The evaluation results indicated that 95% of the participants successfully achieved the expected competencies in terms of knowledge, technical skills, and active participation throughout the training. Participants were able to independently perform all stages of producing fish meatballs and fish satay, from raw material preparation to the final product. Economic analysis further demonstrated that processing fish into meatballs and satay generated an estimated 94% higher profit compared with selling fresh fish directly, highlighting the economic feasibility of product diversification. In addition to improving technical competencies, the program enhanced participants’ understanding of entrepreneurship opportunities based on local fishery resources. Therefore, this training provides an effective community empowerment strategy to increase the added value of fishery products while supporting sustainable household income among fishermen’s families.